Label‐Free Photoelectrochemical Detection of Double‐Stranded HIV DNA by Means of a Metallointercalator‐Functionalized Electrogenerated Polymer. Issue 47 (26th September 2014) - Haddache, Fatima; Le Goff, Alan; Reuillard, Bertrand; Gorgy, Karine; Gondran, Chantal; Spinelli, Nicolas; Defrancq, Eric; Cosnier, Serge
Abstract The design of photoactive functionalized electrodes for the sensitive transduction of double‐stranded DNA hybridization is reported. Multifunctional complex [Ru(bpy‐pyrrole)2(dppn)]2+ (bpy‐pyrrole=4‐methyl‐4′‐butylpyrrole‐2, 2′‐bipyridine, dppn=benzo[i]dipyrido[3, 2‐a:2′, 3′‐c]phenazine) exhibiting photosensitive, DNA‐intercalating, and electropolymerizable properties was synthesized and characterized. The pyrrole groups undergo oxidative electropolymerization on planar electrodes forming a metallopolymer layer on the electrode. Thanks to the photoelectrochemical and intercalating properties of the immobilized RuII complex, the binding of a double‐stranded HIV DNA target was photoelectrochemically detected on planar electrodes. Photocurrent generation through visible irradiation was correlated to the interaction between double‐stranded DNA and the metallointercalator polymer. These interactions were well fitted by using a Langmuir isotherm, which allowed a dissociation constant of 2×106 L mol−1 to be estimated. The low detection limit of 1 fmol L−1 and sensitivity of 0.01 units per decade demonstrate excellent suitability of these modified electrodes for detection of duplex DNA.